Loan Recovery and Sustainability of Microfinance Institutions in Kabale District: A Case Study of Unique SACCO in Kabale Municipality. - Ainembabazi, Ellon (Kabale University, 2023)
Globally, loan recovery is a process involving the procedures the MFI uses to collect its money from debtors and this may take the form of calling clients by telephone, sending reminders letters, contracting collection agencies, and legal actions. Loan recovery may also refer to amount of loans that were previously written off but now collected. In accounting sense, loan recovery involves making accounting entries whereby the sum of money borrowed at a stated rate of interest for a specified period is debited to a loan account and credited to the current account of the clients. The loan is then repaid by regular transfer from current account to loan account over an agreed period. The purpose of this study was to examine loan recovery and sustainability of microfinance institutions in Kabale district a case study of Unique SACCO in Kabale Municipality.